2022
DOI: 10.3390/ijerph19042291
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study on the Effectiveness of Virtual Reality Analgesia for Children and Adolescents with Kidney Diseases Undergoing Venipuncture

Abstract: The current study evaluated the effectiveness of VR analgesia among pediatric and adolescent patients with kidney disease undergoing venipuncture. Patients at an Italian Children’s hospital (N = 82, age range 7–17 years) undergoing venipuncture were randomly assigned to a No VR group (non-medical conversation) vs. a Yes VR group (VR analgesia). After the procedure, patients gave 0–10 Verbal Numeric Pain Scale ratings. Compared with patients in the No VR Group, patients in the Yes VR group reported significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Conversely, onco-hematological patients undergoing venipuncture, experienced no benefit in self-reported pain when exposed to VR implementation; however their Face, Legs, Activity, Cry, Consolability (FLACC) scale during the procedure did not increase, while it increased in the no-distraction group [46]. Both CKD children and cancer patients had significantly reported to have had an overall more enjoyable experience during the venipuncture procedure if exposed to VR [46,47].…”
Section: Paediatricmentioning
confidence: 97%
See 1 more Smart Citation
“…Conversely, onco-hematological patients undergoing venipuncture, experienced no benefit in self-reported pain when exposed to VR implementation; however their Face, Legs, Activity, Cry, Consolability (FLACC) scale during the procedure did not increase, while it increased in the no-distraction group [46]. Both CKD children and cancer patients had significantly reported to have had an overall more enjoyable experience during the venipuncture procedure if exposed to VR [46,47].…”
Section: Paediatricmentioning
confidence: 97%
“…When children suffering from chronic diseases, who are periodically exposed to venipuncture for checking their medical condition, have been considered, two main categories have been studied: chronic kidney diseases (CKD), and cancer patients [46,47]. A parallel RCT including 82 subjects among school-aged children, teen and teenagers with CKD aged between 7 to 17 years old, observed that VR was associated with significantly lower reported 'pain intensity' compared to children exposed to standard of care (non-medical conversation by the nurse in charge of the procedure); in particular, younger children reported a 55% reduction in 'worst pain' during VR, and older children a 35% reduction.…”
Section: Paediatricmentioning
confidence: 99%
“…Aztori et al conducted RCT on children with chronic kidney disease, it involved the use of an immersive VR venipuncture on a psychological pain management strategy during venipuncture, and throughout this process, VR considerably increased fun while significantly reducing the greatest pain and pain unpleasantness. The children who participated in the study were younger than eight years; therefore, they were unable to discern between different pain levels, fear was not examined, and only one venipuncture was used to test pain [ 15 ].…”
Section: Reviewmentioning
confidence: 99%
“… 10 Amongst children and adolescents with kidney disease, significantly reduced pain intensity was reported during venipuncture amongst those who used VR compared to those who did not. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%